Policy Analysis of Unilever Indonesia Company Changes in Fulfilling Consumer Needs During the Covid-19 Pandemic - Anastasya Br Ginting; Nuri Aslami (Journal of Indonesian Management, 2022)
This study examines or analyzes how the Unilever Indonesia Company's policy changes in meeting consumer needs during the COVID-19 pandemic, in this study it will be known what policies and innovations have been carried out by Unilever companies so that the needs of consumers and the company's sustainability will continue in the future. changing conditions due to the COVID-19 pandemic which has almost spread throughout the world. In this study, the research method used is a qualitative approach, descriptive analysis, with secondary data types in the form of research results from various articles, library sources and documents or with literature study data collection techniques. It is known from this research that the presence of COVID-19 greatly affects changes, be it changes in consumer behavior or changes in Unilever's company operations so that appropriate policy changes must be made, such as changes in the form of product sales, which during the pandemic for selling their products all online, for that change and innovations carried out by Unilever companies are by creating E-Commerce services, such as Unilever Home Delivery, Unilever Professionals and Sahabat Warung.